Historical Discourse of Science in India: Colonial Reflections on Present Education System - Tanwar, Shweta (JOURNAL OF INDIAN EDUCATION, 2026)
The pervasive impact of colonisation on today’s education system can be seen through many lenses. Navigating through the journey of science in India during colonial rule, the paper tries to explore the impact of western ideology on the education system of India in contemporary times. The present education system, specifically science education grapples with many issues and challenges that emerged from colonial times. Some problems which require attention in regard to the above discussion are being explored and discussed in the paper.